2005
DOI: 10.1063/1.1839633
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-substituted cobalt ferrite magnetostrictive materials for magnetic stress sensor applications

Abstract: Metal bonded cobaltferrite composites have been shown to be promising candidate materials for use in magnetoelastic stress sensors, due to their large magnetostriction and high sensitivity of magnetization to stress. However previous results have shown that below 60°C" role="presentation" style="box-sizing: borderbox; display: inline; word-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
101
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 239 publications
(113 citation statements)
references
References 10 publications
(9 reference statements)
5
101
0
Order By: Relevance
“…Due to exceptional magnetoelastic, magnetotransport, magnetooptical, photomagnetic, electronic, and magnetic properties, cobalt ferrite ͑CFO͒ has been proposed for applications in noncontact force and torque sensors, 1 as spin filters for magnetic tunnel junctions, 2 for hybrid data storage, 3 for magnetooptical media, 4 and as anode materials for advanced Li-ion batteries. 5 Depending on the requirements of application, magnetic and magnetoelastic properties of CFO can be fine-tuned by appropriate cation substitution 1,[6][7][8] and magnetic annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to exceptional magnetoelastic, magnetotransport, magnetooptical, photomagnetic, electronic, and magnetic properties, cobalt ferrite ͑CFO͒ has been proposed for applications in noncontact force and torque sensors, 1 as spin filters for magnetic tunnel junctions, 2 for hybrid data storage, 3 for magnetooptical media, 4 and as anode materials for advanced Li-ion batteries. 5 Depending on the requirements of application, magnetic and magnetoelastic properties of CFO can be fine-tuned by appropriate cation substitution 1,[6][7][8] and magnetic annealing.…”
Section: Introductionmentioning
confidence: 99%
“…5 Depending on the requirements of application, magnetic and magnetoelastic properties of CFO can be fine-tuned by appropriate cation substitution 1,[6][7][8] and magnetic annealing. 9 The optimum substrate temperature for thin film growth has been reported to be 600°C, 10 in order to produce crystalline CFO.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Substitution of elements such as Mn or Cr for some of the Fe has shown promise of adjusting the magnetic and magnetoelastic properties of these materials through control of chemical composition. 3,4 In order to fully enable the practical applications of these compounds, a more complete family of materials is needed, such that the desired properties can be tailored to a specific application. In the present study, we report on the magnetic characterization of the series of Ga-substituted cobalt ferrites CoGa x Fe 2−x O 4 ͑x = 0.0-0.8͒ as a function of gallium concentration using transmission Mossbauer spectroscopy.…”
mentioning
confidence: 99%
“…The magnetic properties or magneto-optic properties, including the exchange interactions, of these ferrites have been found to be dependent on how the cations are distributed among the two sublattices. [6][7][8] Recently, cobalt ferrite composites 9 and their Mnsubstituted modifications 10 have been actively investigated as part of the development of materials for highly sensitive noncontact stress and torque sensors. It was observed that the substitution of Mn for Fe led to the reduction of both the Curie temperature and the magnetostriction with increasing Mn content.…”
Section: Introductionmentioning
confidence: 99%